INDEPENDENT CURRICULUM MODEL AND LEARNING SYSTEM - Siti Sara (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2025)
The independent curriculum is a curriculum with diverse intracurricular learning where the content will be more optimal so that students have enough time to understand concepts and strengthen competencies. The implementation of the independent curriculum is open to all PAUD, SD, SMP, SMA, Special Education, and Equivalency education units. This curriculum also prioritizes project-based learning strategies. This means that students wil implement the material they have learned through projects or case studies, so that understanding of concepts can be achieved better.